A simplified qPCR method revealing tRNAome remodeling upon infection by genotype 3 hepatitis E virus. Issue 12 (21st March 2020) - Ou, Xumin; Ma, Buyun; Zhang, Ruyi; Miao, Zhijiang; Cheng, Anchun; Peppelenbosch, Maikel P.; Pan, Qiuwei
Abstract : The landscape of tRNA–viral codons regulates viral adaption at the translational level, presumably through adapting to host codon usage or modulating the host tRNAome. We found that the major zoonotic genotype of hepatitis E virus (HEV) has not adapted to host codon usage, prompting exploration of the effects of HEV infection on the host tRNAome. However, tRNAome quantification is largely impeded by the extremely short sequences of tRNAs and redundancy of tRNA genes. Here, we present a length‐extension and stepwise simplified qPCR method that utilizes a universal DNA/RNA hybrid tRNA adaptor and degenerate primers. Using this novel methodology, we observe that HEV infection dramatically reprograms the hepatic tRNAome, which is likely to facilitate translation of viral RNAs. This tRNAome quantification method bears broad implications for future tRNA research and possibly tRNA‐based diagnostics. Abstract :